2016
DOI: 10.1016/j.neuropharm.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Histamine and the striatum

Abstract: The neuromodulator histamine is released throughout the brain during periods of wakefulness. Combined with an abundant expression of histamine receptors, this suggests potential widespread histaminergic control of neural circuit activity. However, the effect of histamine on many of these circuits is unknown. In this review we will discuss recent evidence for histaminergic modulation of the basal ganglia circuitry, and specifically its main input nucleus; the striatum. Furthermore, we will discuss recent findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 170 publications
2
61
0
Order By: Relevance
“…Patients with the W317X mutation of HDC are unable to synthesize histamine and depend on the activity of HDC encoded by the non-mutated second allele. The presence of specific psychiatric comorbidities in some male members of this pedigree could also be explained by a dysfunction in the histaminergic system, as overriding inhibition of competing pathways within parallel cortico-striato-thalamo-cortical loops can hinder behavioral switching as seen in obsessivecompulsive disorder [89]. A more general association of histaminergic pathways with TS was identified by analysis of rare CNVs in a subsequent study [77].…”
Section: Promising Avenues For Researchmentioning
confidence: 91%
See 1 more Smart Citation
“…Patients with the W317X mutation of HDC are unable to synthesize histamine and depend on the activity of HDC encoded by the non-mutated second allele. The presence of specific psychiatric comorbidities in some male members of this pedigree could also be explained by a dysfunction in the histaminergic system, as overriding inhibition of competing pathways within parallel cortico-striato-thalamo-cortical loops can hinder behavioral switching as seen in obsessivecompulsive disorder [89]. A more general association of histaminergic pathways with TS was identified by analysis of rare CNVs in a subsequent study [77].…”
Section: Promising Avenues For Researchmentioning
confidence: 91%
“…Interestingly, we have recently seen increasing consensus that TS is a heterogeneous condition from both the phenotypic and genotypic points of view. Studies conducted using principal-component factor analysis [90][91][92][93][94][95], hierarchical cluster analysis [90,93,94,96] and latent class analysis [97,98] [99], a key region for the pathophysiology of TS, as altered striatal histaminergic-dopaminergic tone has been shown to potentially result in tic generation [89].…”
Section: Promising Avenues For Researchmentioning
confidence: 99%
“…We also examined the Akt target GSK3␤-Ser 9 and found that it, too, was modulated by RAMH treatment (Fig. 4B).…”
mentioning
confidence: 98%
“…Histamine (HA) is produced in the tuberomamillary nucleus of the posterior hypothalamus; these neurons project broadly throughout the brain, including to the striatum (7). HA receptors are prominent throughout the basal ganglia (7,8), but their function in modulating this circuitry is not well understood, and very few studies have examined their functional importance in vivo (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation